INTRODUCTION - LIPTÁK, Michal; VYDROVÁ, Jaroslava (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
Phenomenology originated in the tradition of transcendentalist philosophy, but very soon—already in the works of the founder of phenomenology, Edmund Husserl—it focused on the issue of the body to the extent previously unheard of in transcendentalist philosophy. Crucially, phenomenology never considered a body to be just a kind of tool or mean to be used by “spirit” or the “soul”; rather, the body was analyzed as imbued with an intentionality of its own. Already in Husserl’s works, the most basic structures of our thinking, even the basic logical principles, can be gradually traced back to their roots in bodily experience, perception, or sensation. Later phenomenological philosophy has developed these initial insights in a more detailed manner, and a rich philosophy of the body has arisen in the phenomenological tradition. The thematic volume "Hand – Work/Labor – Matter" is a contribution to this phenomenological philosophy of the body. In general, five studies opening this issue present phenomenological investigations of the body at work. In this work, the body is not just another tool we use. Rather, the body is already who we are. This work of the body is simultaneously a negotiation of our relationship and access to the world; it delineates possibilities for both our practical engagement and our theoretical understanding. The body is co-extensive with the world, and it straightforwardly not only responds to the world as matter but also discloses the world as a matter, too. Any phenomenological investigation of the body at work is therefore always a reflective philosophical investigation as well, a certain retracing of our steps in our self-understanding which ultimately reveals the primordial conditions of our thinking and action.